Bears - Carney, Elizabeth, 1981- (Washington, D.C. : National Geographic, 2016)
"Get ready for a walk on the wild side in this image-packed book all about bears! kids will learn about different kinds of bears, where they live, and what they do. This Level 3 reader is written in an easy-to-grasp style to encourage the animal lovers of today and scientists of tomorrow!"--
Meet the bears -- Big appetites -- Baby bears -- Bears of the world -- Super sleepers -- Cool facts about bears -- A bear's body -- Bears in books -- Bear? think again! -- Bears and people -- The future for bears.
OSLIS\Gale Nat Geo eBooks(2/2/23).
Includes index.
Ages 6-9.
Description based on print version record.
Keywords: Bears -- Juvenile literature; Bears; Bears; Bears; JUVENILE NONFICTION / Animals / Bears; JUVENILE NONFICTION / Reader - Intermediate; JUVENILE NONFICTION / Science & Nature / Zoology; Electronic books- OSLIS; Juvenile works; Electronic books